A Study of Handover Performance in Both SA & NSA Architectures as a Step to Achieve Load Balancing in 5G Wireless Networks - دوبا, لمى; أحمد محمود أحمد; أحمد صقر أحمد (Latakia University Journal -Engineering Sciences Series, 2022)
Mobility Load Balancing (MLB) and Handover Management in 5G networks are among the most important issues of interest to researchers and cellular network operators, because of their impact on Quality of Service and Resource Efficiency. achieving Load Balancing in 5G networks depends on a process called Offloading,Which is based on the displacement of users from an Overloaded cell to an under-loaded neighboring cell by modifying the Handover parameters,to force users to move to a neighboring cell and thus changing the serving base station. This paper presents a study of the two 5g architectures which are proposed by 3GPP (Third Generation Partnership Project),The Standalone and Non-Standalone architectures, and an evaluation of the performance of Handover process in each of them. It also presents a study of the Handover parameters and their role in Offloading as a step to achieve Load Balancing.the performance of the Handover and Offloading process in both architectures are evaluated in terms of throughput and latency. The results show that the performance of the Handover and Offloading processes in the Standalone architecture is better than the Non-Standaone architecture according to the two studied performance evaluation metrics.